From village elder to British judge: custom, customary law, and tribal society - Asoka Kumar Sen (New Delhi: Orient Blackswan, 2012)
Examines the definition and redefinition of customary law in the context of the adivasis of Jharkhand during pre-colonial and colonial times.
Keywords: Customary Law Jharkhand; Tribes Jharkhand; Tribal Society Law; Tribal Custom Jharkhand; Law; Social Sciences